In vitro and in vivo characterization of dmHexDC function - Erkol, Emir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2019)
Glycosylation of molecules is crucial for a wide variety of cellular processes ranging from cell-cell communication to cell differentiation and is altered in many neurodevelopmental disorders. β-hexosaminidases process glycoconjugates by hydrolyzing the catalysis of terminal N-acetyl-β-D-hexosamine residues found at the non-reducing end of glycans. Previously, three hexosaminidases were characterized in Drosophila melanogaster that cleave N-acetyl-β-D-glucosamine residues. Our group identified a new putative hexosaminidase, dmHexDC, which is expressed in R7 photoreceptors and preneuronal cells in the eye imaginal disc of Drosophila. In order to gain functional insight into the role of dmHexDC in neurodevelopment, I characterized the biochemical function of dmHexDC and showed that it removes both terminal N-acetyl-β-D-glucosamine and Nacetyl-β-D-galactosamine residues in vitro. Even though dmHexDC is able to remove both substrates, its substrate specificity is towards N-acetyl-β-D-galactosamine residues. Furthermore, a homology model of dmHexDC was generated and the output structure resembled a (β/α)8-barrel topology, which is a common structure among GH20 family proteins. The key residues that partake in the catalytic activity of dmHexDC was investigated from the homology model and glutamic acid at amino acid position 347 was identified as the general acid/base residue. Furthermore, E347A mutants displayed diminished catalytic activity towards the N-acetyl-β-D-hexosamine substrates. This suggested that integrating E347A mutation in vivo would create a hypomorph for dmHexDC. In order to generate fast and efficient dmHexDC mutants for functional studies in vivo, I generated a recombinase mediated cassette exchange (RMCE) template mutant by excising dmHexDC out and integrating white gene flanked by inverted attP sites using the CRISPR/Cas9 gene editing method. Any DNA of interest can be integrated to the dmHexDC gene region of the mutant by cassette exchange with high efficiency. Flies homozygous for the mutant allele were observed to viable and I showed that homozygous mutants lacking dmHexDC has mild neuronal loss at the ventral side of the eye imaginal discs.
Keywords: Glycosylation.